Tetraploidy Confers Superior in vitro Water-Stress Tolerance to the Fig Tree (Ficus carica) by Reinforcing Hormonal, Physiological, and Biochemical Defensive Systems - Abdolinejad, Ruhollah; Shekafandeh, Akhtar (Frontiers in Plant Science, 2022)
The fig tree is a well-adapted and promising fruit tree for sustainable production in arid and semi-arid areas worldwide. Recently, Iran’s dryland fig orchards have been severely damaged due to prolonged severe and consecutive drought periods. As emphasized in many studies, ploidy manipulated plants have a significantly enhanced drought tolerance. In the current study, we compared the induced autotetraploid explants of two fig cultivars (‘Sabz’ and ‘Torsh’) with their diploid control plants for their water stress tolerance under in vitro conditions using different PEG concentrations (0, 5, 10, 15, 20, and 25%). After 14 days of implementing water stress treatments, the results revealed that both tetraploid genotypes survived at 20% PEG treatments. Only ‘Sabz’ tetraploid explants survived at 25% PEG treatment, while both diploid control genotypes could tolerate water stress intensity only till 15% PEG treatment. The results also demonstrated that the tetraploid explants significantly had a higher growth rate, more leaf numbers, and greater fresh and dry weights than their diploid control plants. Under 15% PEG treatment, both tetraploid genotypes could maintain their RWC at a low-risk level (80-85%), while the RWC of both diploid genotypes drastically declined to 55-62%. The ion leakage percentage also was significantly lower in tetraploid explants at 15% PEG treatment. According to the results, these superiorities could be attributed to higher levels of stress response hormones including abscisic acid, salicylic acid, and jasmonic acid at different PEG treatments, the robust osmotic adjustment by significantly increased TSS, proline, and glycine betaine contents, and augmented enzymatic defense system including significantly increased SOD, CAT, APX, and GPX activities in tetraploid genotypes, compared to their diploid control genotypes. Consequently, the current study results demonstrated that ‘Sabz’ tetraploid genotype had a significantly higher water stress tolerance than other tested genotypes.